Teaching strategies and activities used for students' clinical placement in residential aged care facilities: a scoping review protocol. Issue 5 (May 2020) - McCloskey, Rose; Keeping-Burke, Lisa; Donovan, Cindy; Witherspoon, Richelle; Cook, Jessica; Lignos, Nicholas
ABSTRACT: Objective: The objective of this scoping review is to examine and map current knowledge of teaching strategies and activities used with nursing students during clinical placements in residential aged care facilities. Introduction: Residential aged care facilities provide opportunities for nursing students to develop skills and interest in caring for older adults. Studies that address students' clinical placements in these settings highlight the benefits of and concerns with their experiences. Insight into the state of knowledge regarding teaching strategies used in residential aged care facilities could benefit nursing education programs and help to ensure student learning is maximized. Inclusion criteria: This scoping review will consider research and narrative reports on teaching activities and strategies used by nursing faculty and residential aged care facility staff in teaching nursing students. The concepts of interest include planned and intentional activities and strategies used to facilitate student learning and student clinical experiences. A clinical experience is defined as when a student enters a residential aged care facility and is assigned an individual or individuals to care for. Methods: This scoping review will aim to locate published and unpublished literature employing a three-step search strategy. Only papers published in English from 1992 onward will be included. Data extracted from eligible papers will include details on the participants, context, strategy, activity and outcomes. Extracted data will be reported in a tabular form and presented narratively to address the review objective.